Treatable Cause of Dilated Cardiomyopathy, Rickets; Two Years' Experience - Nihal Akçay; Ülkem Koçoğlu Barlas; Esra Deniz Papatya Çakır; Mey Talip Petmezci; Hasan Serdar Kıhtır; Osman Yeşilbaş; Bedir Akyol; Esra Şevketoğlu (Galenos Yayinevi, 2022)
Objective:Dilated cardiomyopathy (DC) results from dilatation of one or both ventricles and is caused by systolic dysfunction. Rickets are a rare cause of DC. Here, we present a case series of DC due to rickets, which was successfully treated.Materials and Methods:Patients were followed-up at paediatric intensive care unit (ICU) with the diagnosis of DC-related heart failure, which was retrospectively evaluated. Patients with a disease other than hypocalcaemia and low vitamin D levels, which can cause heart failure, were excluded from this study.Results:Six patients who developed rickets-related heart failure were included in this study. The mean age of the patients was 6.4±3.2 months. All patients had growth developmental delay. Although most of the patients were admitted to the hospital due to respiratory distress, congestive heart failure findings were detected at the first examination of all the patients. The vitamin D levels of all patients were low. While the pre-treatment mean ejection fraction (EF) of the patients was 35.16% (±10.66), the post-treatment mean EF was found to be 55% (±9.83). Significant improvement in left ventricular function was observed post-treatment.Conclusion:In patients admitted to the ICU due to the diagnosis of heart failure, rickets should be considered and treated, considering that it can cause many other complications, including vitamin D deficiency, cardiomyopathy and cardiac dysfunction.